Surface electromyography of nine shoulder muscles in two iron cross conditions in gymnastics - Bernasconi, S.; Tordi, N.; Parratte, B.; Rouillon, J.-D.; Monnier, G. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: The rules of gymnastics impose an element of static strength such as an iron cross (IC) on the rings. For IC training, coaches use a custom made device -- the herdos -- to simulate the conditions of competition. The purpose was to compare muscle activity and coordination during IC performed both on the rings and using herdos. Secondly, we tried to determine whether herdos usage induced functional adaptations of the shoulder muscles. METHODS: Six male gymnasts performed 10 IC in each condition. Surface electromyogram of muscles pectoralis major, latissimus dorsi, teres major, infraspinatus, rhomboideus, trapezius, serratus anterior, biceps brachii, and triceps brachii in the right shoulder were analysed using root-mean-square (RMS), and muscle part's in each condition. Muscle part represents the contribution of each of the 9 shoulder muscles studied in each condition. Total muscle activity (SUM) was also used to compare the 2 conditions. RESULTS: Except for the muscle teres major, the RMS decreases (p<0.05) when using the herdos. The SUM also decreases (p<0.05) when using this device. The muscle parts indicate that the contribution of the muscle latissimus dorsi decreases (p<0.05) when using the herdos. These results suggest that the herdos modified shoulder coordination. But their usage does not seem to induce any functional adaptations of these muscles. CONCLUSIONS: The herdos do not seem to provide a valid method to reproduce the same shoulder coordination as on the rings. Therefore IC training with this special device could be called in question.